Target Capital Structure Determinants and Speed of Adjustment Analysis to Address the Keynes-Hayek Debate - Getzmann, André; Sebastian Lang, Sebastian Lang; Klaus Spremann, Klaus Spremann (Journal of Reviews on Global Economics, 2015)
According to F. A. Hayek, Keynes' General Theory neglects an analysis of the production structure. As a contribution to this research gap, we look at companies' decisions to finance investments and at their agility to adjust their capital structure. We thus study the relationship between capital structure to finance corporate production and shifts in aggregate demand. Target capital structure determinants and speeds of adjustment to these target capital structures will be analyzed for a geographically comprehensive sample of 2,706 companies listed in Asia, Europe and the U.S.A. in the period 1995 – 2009. Aggregate demand turns out to be the coordinating force which determines managers' choices of target capital structures. The speed of adjustments towards target capital structures indicate that firms are agile in adapting to their targets. Our results provide evidence on Keynes' General Theory from a firm level perspective: Firms respond quickly to shifts in aggregate demand by adjusting capital and production structure correspondingly.